Effects of Mykovam, BioN and inorganic fertilizers on growth, yield and nutrient status of sweet sorghum [Sorghum bicolor (L.) Moench] - Aggangan, Nelly S.; Calayag, Miguel Luigi L.; Salvan, Austin Japeth R.; Velandres, John Carlo (2011)
Sorghum is an important crop to dryland farmers and can be utilized for feeds and biofuel. This study was conducted to determine the effects of biofertilizers Mykovam and Bio-N on growth, yield, and nutrient uptake of Sweet Sorghum. The efficiency of biofertilizers was also compared with that of chemical fertilizers. Sweet sorghum was applied with biofertilizers Mykovam (containing mycorrhizal fungi) or BioN (containing nitrogen fixing bacteria), with or without half or full rte of the recommended rate of chemical fertilizer (RRC = 60-60-60 NPK). The experiment was conducted at the Demonstration farm of BIOTECH, UP Los Baños following a RCBD with four blocks. Growth was monitored periodically and plant samples were harvested at 102 and 154 days. Fresh and dry biomass, juice from the stalk, brix level and plant N and P status were measured. Results shows that Mykovam+BioN promoted the largest root collar diameter. Mykovam alone and BioN+Mykovam promoted the highest fresh and dry weights of leaves, roots, and cane, cumulatively, the highest total biomass. Mykovam treated sorghum had the highest total N and P uptake (1,707 g N/plant and 269 g P/plant) and the lowest was obtained from the control plants (999 g N/plant and 214 g P/plant). The highest fruit yield was obtained from plants treated with RRC (16.10 g/cane) comparable with BioN+Mykovam+1/2RRC (13.24 g/cane) and the lowest was the control (3.97 g/cane). In terms of brix level at 102 days, RRC gave the highest (9.36) comparable with BioN+Mykovam+1/2RRC treated plants (8.80) and the lowest was (6.20). At 145 days, Mykovam+Bion+1/2RRC treated plants had the highest (14.52) brix and the lowest was the control (13.72). The high nutrient status and brix level due to Mykovam+BioN+1/2RRC suggests that sweet sorghum can be a feasible source of feed and biofuel.
Keywords: Sorghum; Mykovam; Mycorrhizal fungi; Fertilizer application